Pengaruh Media Gambar Terhadap Keterampilan Menulis Puisi Pada Siswa Kelas V - Qory Nur Khofifah; Eva Herdiyana (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
This study uses a qualitative research approach with a descriptive type. The purpose of this study was to prove the effect of picture media on poetry writing skills in class V. In addition, the purpose of this study was to prove that pictures can be a medium for learning to write poetry. This research also proves that by using image media for poetry writing skills, children's learning outcomes increase. Data collection techniques in this study also used document study techniques using data from previous research journals related to the title. Based on the results of the study, it can be concluded that this picture media succeeded in making children interested and motivated to develop their writing skills, including writing poetry. Media images also affect children's learning outcomes can make passive children become active. This writing skill must always be trained so that children can write fluently and proficiently with or without media.